Critical Thinking Learning Video on Local Wisdom Issues in Writing Argumentative Paragraph - Yamin, Moh.; Taqwiem, Ahsani; Faradina, Faradina; Ramadhani, Fahmi; Abidin, Ahmad Zainul (English Teaching Journal : A Journal of English Literature, Language and Education, 2023)
The presence of learning videos for achieving student learning outcomes is one of the keys to achieving appropriate learning goals and objectives. Teaching students to write argumentative paragraphs needs to be supported by learning videos to help students understand and practice learning to write paragraphs. Bringing the material closer to learning videos with local issues is an inseparable part of introducing and familiarizing students with the environment so that they become an inseparable part of the environment itself. This research aimed to develop critical thinking learning videos containing local wisdom issues in argumentative paragraph writing. The research design used is R & D (Research & Development) with the ADDIE model with stages including (1) conducting needs analysis, (2) developing video products, (3) designing and conducting formative evaluations, (4) revising products, and (5) conducting summative evaluations or product trials, that are tested on small groups so that they can still get feedback for improving the product. The results of the research show that the critical thinking learning video containing local wisdom issues in the argumentative paragraph writing that has been created fulfills the elements. It is appropriate for use in critical thinking learning containing local wisdom issues in the material of writing argumentative paragraphs based on the results of needs analysis, carrying out product trials, and validating from experts and revising the product based on the validation results.